2015
DOI: 10.1038/npjpcrm.2014.101
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of an Asthma/COPD service for primary care: a cross-sectional baseline description and longitudinal results

Abstract: Background:In 2007, an Asthma/chronic obstructive pulmonary disease (COPD) (AC) service was implemented in the North of the Netherlands to support General Practitioners (GPs) by providing advice from pulmonologists on a systematic basis.Aims:To evaluate the feasibility and effectiveness of this service on patient-related outcomes.Methods:We report baseline data on 11,401 patients and follow-up data from 2,556 patients. GPs can refer all patients with possible obstructive airway disease (OAD) to the service, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 27 publications
(32 reference statements)
0
50
1
2
Order By: Relevance
“…Indeed, in a recent study performed in 12 primary care practices in the UK showed considerable more patients with an ACQ score<2.0 than in our observation (79% versus 43%) [25]. Another study, carried out in primary care in the Netherlands by Metting et al showed fewer patients with uncontrolled asthma (39% versus 65%) compared to the number in our study [26]. Specific features of the asthma such as presence of exercise induced bronchoconstriction, time of onset of asthma and the medication regime patients were actually on at the time of referral to secondary care were not systematically collected in the present study.…”
Section: Strengths and Limitations Of This Studycontrasting
confidence: 70%
“…Indeed, in a recent study performed in 12 primary care practices in the UK showed considerable more patients with an ACQ score<2.0 than in our observation (79% versus 43%) [25]. Another study, carried out in primary care in the Netherlands by Metting et al showed fewer patients with uncontrolled asthma (39% versus 65%) compared to the number in our study [26]. Specific features of the asthma such as presence of exercise induced bronchoconstriction, time of onset of asthma and the medication regime patients were actually on at the time of referral to secondary care were not systematically collected in the present study.…”
Section: Strengths and Limitations Of This Studycontrasting
confidence: 70%
“…This might have been caused by the diagnostic variation among pulmonologists, which was previously described by M etting et al [7]. Despite this diagnostic variation between the pulmonologists, additional data from 1856 patients showed that most diagnoses were confirmed at follow-up (confirmed in 92% of the asthma patients, in 86% of the COPD patients and in 73% of the ACOS patients).…”
Section: Discussionmentioning
confidence: 88%
“…Pulmonologists assess these patient data through an online secured internet portal and send a diagnosis and management recommendation to the GP. Currently, 11,000 patients have been assessed by the AC-service, and it is considered to be feasible and effective 14. Comparable outcomes may be expected for the AMSS when it is implemented in a broader fashion.…”
Section: Discussionmentioning
confidence: 99%